PERCEPTION OF STUDENTS, TEACHERS, ADMINISTRATORS AND THEIR RELATIONSHIP OF QUALITY OF SERVICE AT THE NATIONAL UNIVERSITY SAN LUIS GONZAGA, 2024 - Mejía, Mario Gustavo Reyes; Hinojosa, César Trujillo; Reyes, Rosa Elvira Ruiz; Ruiz, Mtro. Cleidy Sofía Farfán; Ccolque, Jose Yudberto Vilca; Cueto, Benito Armando Larroche; Samanamud, Luis Alberto Castillo (Journal of Posthumanism, 2025)
The objective of this study is to examine how users perceive the quality of the service offered by Electrocentro S.A., using the SERVQUAL model as a reference. A quantitative method was chosen, with a descriptive and non-experimental design, and a sample of 384 users who were treated at the Huancayo customer service office was used. A structured questionnaire was used and validated for data collection, which were analyzed using descriptive and inferential statistics. The findings show that the dimensions of reliability, responsiveness, safety, empathy and tangible aspects present notable differences between what users expected and what they actually perceived, suggesting the existence of a negative gap in perceived quality. It is concluded that there is a medium level of general satisfaction, highlighting the need to implement strategies that improve customer service, optimize internal processes and strengthen communication within the organization to raise service quality standards.